Mitigating Heat Exposure: Exploring the Role of Knowledge, Risk Perception, and Precautionary Behavior - Permatasari, Noviyanti; Yovi, Efi Yuliati; Kuncahyo, Budi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Increasing ambient temperatures due to climate change have significantly impacted workers’ physical and mental workloads, affecting their health and safety. Promoting precautionary behaviors, especially among outdoor workers, is an effective strategy widely recommended for addressing these challenges. Precautionary behavior represents an essential protective mechanism that can be adopted at the individual level. This study explores the connections among Occupational Safety and Health (OSH), risk perception, and precautionary behavior. Descriptive statistics and Structural Equation Modeling with the Partial Least Squares approach were used to analyze the data. This study was conducted at two forest management units in Central Java and East Java, Indonesia, where daily air temperatures are relatively high. The research involved 100 respondents, comprising 50 indoor and 50 outdoor workers. The findings of this investigation reveal that OSH-related knowledge among indoor workers predicts their precautionary behavior. Nevertheless, according to the model, attempts to improve precautionary behavior through knowledge enhancement are estimated to be unsuccessful among outdoor workers. Nonetheless, OSH-related knowledge can facilitate workers in developing a more realistic perception, especially regarding the “dread risk factor” among forestry workers, which can positively impact their precautionary behavior. Keywords: forestry worker, heat exposure, mediation analysis, occupational health, psychometrics paradigm